2023
DOI: 10.1177/10497323231172880
|View full text |Cite
|
Sign up to set email alerts
|

Video Conferencing Peer Support and Rarer Forms of Dementia: An Exploration of Family Carers’ Positive Experiences

Abstract: Little is known regarding the nuanced experiences of family carers for people living with rare dementias (PLWRD), with no known literature exploring their positive experiences of caring discussed within peer support group settings. This article explores family carers of PLWRD’s positive experiences reported in video conferencing peer support groups. Six peer support group sessions involving a total of nine participants were qualitatively analysed using thematic analysis, guided by the conceptual framework of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…The majority of articles addressing group activities reported that participants in online groups experienced interpersonal aspects similar to those in face-to-face groups, e.g., a sense of togetherness. This observation supports similar trends identified in general findings on the conduct of various online support group formats, that have emerged independently of the COVID-19 pandemic [41][42][43]. Consequently, online groups may indeed serve as adequate alternatives to face-to-face group activities of POs.…”
Section: Positive Outcomes Challenges and Facilitating Factorssupporting
confidence: 88%
“…The majority of articles addressing group activities reported that participants in online groups experienced interpersonal aspects similar to those in face-to-face groups, e.g., a sense of togetherness. This observation supports similar trends identified in general findings on the conduct of various online support group formats, that have emerged independently of the COVID-19 pandemic [41][42][43]. Consequently, online groups may indeed serve as adequate alternatives to face-to-face group activities of POs.…”
Section: Positive Outcomes Challenges and Facilitating Factorssupporting
confidence: 88%
“…As with many of the studies highlighted in this systematic review, Gerritzen et al 90 also noted the advantages of online groups compared to in-personspecifically not having to travel and the greater potential to develop ad hoc relationships outside of support group meetings. Rapley et al 91 also demonstrated positive responses when exploring the use of videoconferencing for peer support among family carers of people with rarer dementia. Across interviews with nine carers, participants emphasised that digital peer support helped them to maintain their relationship with their cared for person, demonstrate and acknowledge compassion from others, take time to have a personal life and balance this alongside caring, as well as being cognisant of the role they are in and maintaining positivity in it.…”
Section: Notable Studiesmentioning
confidence: 99%